Agenda setting, policies and political systems : a comparative approach - Walgrave, Stefaan (Colección de libros electrónicos de ULoyola, 2014)
Before making significant policy decisions, political actors and parties must first craft an agenda designed to place certain issues at the center of political attention. The agenda-setting approach in political science holds that the amount of attention devoted by the various actors within a political system to issues like immigration, health care, and the economy can inform our understanding of its basic patterns and processes. While there has been considerable attention to how political systems process issues in the United States, Christoffer Green-Pedersen and Stefaan Walgrave demonstrate the broader applicability of this approach by extending it to other countries and their political systems. Agenda Setting and Political Attention brings together essays on eleven countries and two broad themes.